Genomics and democracy : towards a 'lingua democratica' for the public debate on genomics - Derkx, Peter, 1951-; Kunneman, Harry, 1948- (Life Sciences, Ethics and Democracy, 2013)
This book addresses the ethical and political questions flowing from the vastly increased possibilities to manipulate the genetic properties of organisms, including human beings. Due to the great complexity of the scientific fields involved, these questions are framed and answered mostly by scientific experts. But the new technological possibilities and social practices connected with genetic manipulation intrude into domains that for a long time have been the provenance of religious and secular worldviews and touch upon deep-seated convictions and emotions. Moreover they are strongly influenced by economic and political interests. As a consequence, questions of scientific truth and technical control are getting more and more mixed up with questions regarding values and interests. Against this background, this book starts from the premise that neither clinging to the idea of value-neutral, disinterested science, nor the complete abandonment of this idea in favour of postmodern relativism will be of much help here. Instead the different contributions to this book explore the idea of a 'lingua democratica' for the life sciences and sketch the contours of this notion by focusing on a broad range of conceptual and practical issues in the field of genomics.